PERAN MEDIA KOMIK EDUKATIF DALAM MENINGKATKAN MINAT MEMBACA SISWA FASE B : KAJIAN PUSTAKA - Nor Alifa Khalida; Amisha Ramadhayanti; Cindy Syahita Azzahra; Muhammad Ihsan Haris; Ahmad Suriansyah; Maimunah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the influence of educational comic media on the reading interest of Phase B elementary school students. The research was conducted through a literature review by examining various previous studies related to children’s literacy development. The findings indicate that educational comics play a significant role in enhancing students’ reading interest through the combination of engaging, simple, and contextually relevant text and illustrations. This medium successfully transforms students’ perception of reading from a monotonous task into an enjoyable and meaningful activity. Furthermore, the characteristics of Phase B students’ reading interest are influenced by factors such as the implementation of reading programs, the presence of reading corners at schools, and the broader cultural context of literacy in Indonesia. Educational comics have also been proven effective in fostering intrinsic motivation, improving reading comprehension, and strengthening students’ emotional engagement with texts. Therefore, educational comics can serve as an innovative solution to promote a culture of literacy in elementary schools while supporting the development of students’ character and critical thinking skills.